(untitled) (European Journal of Marketing and Economics, 2024)
This study investigates the determinants of creditworthiness and loan repayment performance among 113 small-holder agricultural loan borrowers from the SANASA TCCS in five villages within Sri Lanka’s Vavuniya district. Using a structured questionnaire, primary data was collected during 2018/2019. The study employs a binary probit model, with creditworthiness defined as a binary variable (1 for defaulters, 0 for non-defaulters), examining its relationship with demographic, farming, and farmer attribute variables. Descriptive statistics reveal that 43.4% of respondents were defaulters, while 56.6% were non-defaulters. Probit model results indicate several significant factors influencing repayment performance. Among demographic characteristics, age, education level, and number of family members positively impacted repayment. For farming characteristics, income, farm size, land ownership, farming experience, engagement in off-farm activities, loan purpose, and perceived possibility of crop failure positively influenced creditworthiness and repayment at varying significance levels. Additionally, farmers’ knowledge about the loan terms and the presence of responsible guarantors were crucial farmer attributes affecting repayment. These findings offer valuable insights for both small-holder farmers and microfinance institutions, enabling better prediction of repayment behavior among new loan applicants and informing future lending decisions.